The effect of work environment, communication, and workload on employee performance case study PT. Setia Kawan Abadi year 2022 - Abdul Rahman Yusuf; Adrian Adrian (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study aims to determine the effect of work environment, communication, and workload on employee performance at PT. Setia Kawan Abadi. Work environment, communication, and workload are independent variables, during employee performance is a dependent variable. The population of this study was employees at PT. Setia Kawan Abadi. The type of research used is quantitative; the data used in this study is primary data from respondents' answers to the questionnaire and processed using SPSS software version 28. Furthermore, the sampling technique used is census or total sampling with the number of respondents obtained by 55 employees of PT. Setia Kawan Abdi. The study’s results based on the t-test (Partial) prove that the work environment on employee performance has a positive and insignificant effect. At the same time, communication and workload significantly positively impact employee performance. The variables of work environment, communication, and workload simultaneously affect employee performance.